2005
DOI: 10.1111/j.1365-2052.2005.01387.x
|View full text |Cite
|
Sign up to set email alerts
|

Mapping QTLs on chicken chromosome 1 for performance and carcass traits in a broiler x layer cross

Abstract: With the objective of mapping quantitative trait loci (QTLs) for performance and carcass traits, an F2 chicken population was developed by crossing broiler and layer lines. A total of 2063 F2 chicks in 21 full-sib families were reared as broilers and slaughtered at 42 days of age. Seventeen performance and carcass traits were measured. Parental F(0) and F1 individuals were genotyped with 80 microsatellites from chicken chromosome 1 to select informative markers. Thirty-three informative markers were used for s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
89
1
12

Year Published

2007
2007
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 82 publications
(111 citation statements)
references
References 23 publications
9
89
1
12
Order By: Relevance
“…They found that a significant QTL controlling abdominal fat rate at 70 d of age was located at 241 cM (MCW0058-MCW0101), and a suggestive QTL for abdominal fat weight at 70 d of age was located at 214 cM (LE10174-ADL0361) [10]. Nones et al [15] also reported a QTL for abdominal fat weight located on GGA1 at 194 cM (ADL0020-LEI0160). In the present study, we identified four QTL for fat traits, a significant QTL at a 1% genome-wise level for abdominal fat weight, two significant QTL at a 5% genome-wise level for abdominal fat rate and fat width, and a suggestive QTL for fat thickness under the skin.…”
Section: Discussionmentioning
confidence: 90%
“…They found that a significant QTL controlling abdominal fat rate at 70 d of age was located at 241 cM (MCW0058-MCW0101), and a suggestive QTL for abdominal fat weight at 70 d of age was located at 214 cM (LE10174-ADL0361) [10]. Nones et al [15] also reported a QTL for abdominal fat weight located on GGA1 at 194 cM (ADL0020-LEI0160). In the present study, we identified four QTL for fat traits, a significant QTL at a 1% genome-wise level for abdominal fat weight, two significant QTL at a 5% genome-wise level for abdominal fat rate and fat width, and a suggestive QTL for fat thickness under the skin.…”
Section: Discussionmentioning
confidence: 90%
“…Some QTLs mapped in this population have been described by Nones et al (2006), Ambo et al (2009) and Campos et al (2009). Procedures seeking to reduce the occurrence of false positives or negatives were not employed in these studies, except of course to adjust the level of type I error to an acceptable level.…”
Section: Introductionmentioning
confidence: 99%
“…Both pure lines were developed by the Embrapa Swine and Poultry Research Centre and were under multitrait selection for six (TT) and eight (CC) generations when the F2 population was created (details are in Nones et al 2006). A total of 2,063 F2 chickens were obtained from 17 hatches during 8 months, from 21 full-sib families.…”
Section: Population and Traitsmentioning
confidence: 99%
“…A total of 2,063 F2 chickens were obtained from 17 hatches during 8 months, from 21 full-sib families. Seven of these families (652 F2 chickens) were used in the QTL mapping study (Nones et al 2006). …”
Section: Population and Traitsmentioning
confidence: 99%
See 1 more Smart Citation